Structural basis for PtdInsP2-mediated human TRPML1 regulation. Issue 1 (December 2018) - Fine, Michael; Schmiege, Philip; Li, Xiaochun
Abstract Transient receptor potential mucolipin 1 (TRPML1), a lysosomal channel, maintains the low pH and calcium levels for lysosomal function. Several small molecules modulate TRPML1 activity. ML-SA1, a synthetic agonist, binds to the pore region and phosphatidylinositol-3, 5-bisphosphate (PtdIns(3, 5)P2 ), a natural lipid, stimulates channel activity to a lesser extent than ML-SA1; moreover, PtdIns(4, 5)P2, another natural lipid, prevents TRPML1-mediated calcium release. Notably, PtdIns(3, 5)P2 and ML-SA1 cooperate further increasing calcium efflux. Here we report the structures of human TRPML1 at pH 5.0 with PtdIns(3, 5)P2, PtdIns(4, 5)P2, or ML-SA1 and PtdIns(3, 5)P2, revealing a unique lipid-binding site. PtdIns(3, 5)P2 and PtdIns(4, 5)P2 bind to the extended helices of S1, S2, and S3. The phosphate group of PtdIns(3, 5)P2 induces Y355 to form a π-cation interaction with R403, moving the S4–S5 linker, thus allosterically activating the channel. Our structures and electrophysiological characterizations reveal an allosteric site and provide molecular insight into how lipids regulate TRP channels. Transient receptor potential mucolipin 1 (TRPML1) is a lysosomal channel which maintains the low pH and calcium levels for lysosomal function. Here authors use structural biology and electrophysiology to show how lipids bind and allosterically activate TRPML1.